Vocal Stereotypy and Autism Spectrum Disorder: A Systematic Review of Interventions. (October 2020) - Wang, Danni; Mason, Rose A.; Lory, Catharine; Kim, So Yeon; David, Marie; Guo, Xiaojie
Highlights: The evidence base indicates a functional relation between implementation of motor response interruption and redirection and decreases in vocal streotypy Evidence for auditory stimulus-based interventions is promising Sensory integration and auditory integration training are ineffective in decreasing vocal stereotypy Evidence on effective interventions to decrease vocal stereotypy for adolescents and adults with autism is limited Abstract: Background: Individuals with autism spectrum disorder (ASD) often engage in vocal stereotypy (VS), which hinders inclusion in educational activities and may lead to poor social and adaptive outcomes. Interventions that address VS in individuals with ASD have been examined for a few decades. However, there are no current reviews that evaluate the methodological rigor of the empirical literature and provide a synthesis of the evidence based on high-quality research. Therefore, the present review aimed to evaluate the quality of VS interventions for individuals with ASD, summarize the characteristics of studies that demonstrate quality, and determine the strength of evidence. Method: Systematic search procedures were implemented and articles were identified based on predetermined inclusion criteria. Sixty studies were included for quality evaluation against the What Works Clearinghouse single-case research design standards, of which 39 studies were further synthesized. Results: Findings indicate response interruption and redirection, auditory stimulus-based and consequence based interventions to be promising with moderate to strong effects, whereas sensory integration interventions have no empirical support. However, majority of the interventions were implemented by researchers rather than practitioners and few studies addressed social validity. Conclusions: While much of the VS literature demonstrates strong internal validity, we encourage future researchers to investigate the efficacy and feasibility of these interventions when implemented by practitioners and parents. Additionally, assessment of social validity of the interventions is strongly encouraged. We also recommend that practitioners consider the strength of intervention effect when making treatment selection decisions.